Genomic and Transcriptomic Evidence Supports Methane Metabolism in Archaeoglobi - Yi-Fan Liu (American Society for Microbiology, 2020)
ABSTRACT Euryarchaeal lineages have been believed to have a methanogenic last common ancestor. However, members of euryarchaeal Archaeoglobi have long been considered nonmethanogenic and their evolutionary history remains elusive. Here, three high-quality metagenomic-assembled genomes (MAGs) retrieved from high-temperature oil reservoir and hot springs, together with three newly assembled Archaeoglobi MAGs from previously reported hot spring metagenomes, are demonstrated to represent a novel genus of Archaeoglobaceae, “Candidatus Methanomixophus.” All “Ca. Methanomixophus” MAGs encode an M methyltransferase (MTR) complex and a traditional type of methyl-coenzyme M reductase (MCR) complex, which is different from the divergent MCR complexes found in “Ca. Polytropus marinifundus.” In addition, “Ca. Methanomixophus dualitatem” MAGs preserve the genomic capacity for dissimilatory sulfate reduction. Comparative phylogenetic analysis supports a laterally transferred origin for an MCR complex and vertical heritage of the MTR complex in this lineage. Metatranscriptomic analysis revealed concomitant in situ activity of hydrogen-dependent methylotrophic methanogenesis and heterotrophic fermentation within populations of “Ca. Methanomixophus hydrogenotrophicum” in a high-temperature oil reservoir. IMPORTANCE Current understanding of the diversity, biology, and ecology of Archaea is very limited, especially considering how few of the known phyla have been cultured or genomically explored. The reconstruction of “Ca. Methanomixophus” MAGs not only expands the known range of metabolic versatility of the members of Archaeoglobi but also suggests that the phylogenetic distribution of MCR and MTR complexes is even wider than previously anticipated.